The relationship of Self-confidence to self esteem among students of the Institute of Sciences and Technical of Physical and Sport Activities . - بن عطاء الله, محمد; رافع , أحمد (sports creativity, 2025)
The present study aims to know the relationship between Self-confidence and self esteem of the students of the Institute of Sciences and Technical of Physical and Sport Activities at the University of Bouira, The two researchers used the descriptive approach to achieve the objectives of the study and the application of the self confidence scale and the self esteem on a random sample of 40 students, The results were summarized and analyzed using statistical analysis is social sciences program (spss), The results showed a statistically significant correlation between self confidence and self esteem, Accordingly Accordingly the researchers recommended Work on designing programs that help develop the self-confidence of university students, and work on enhancing their self-confidence, Providing the necessary capabilities and means to activate the extension services in educational institutions in all academic levels.